Experiences of pregnant and parenting students at a university in Gauteng province - Moroti E. Mahlangu; Tshiamo N. Ramalepa; Lucky O. Letswalo (AOSIS, 2024)
Background: Pregnancy and parenting in tertiary institutions is a worldwide concern. The number of pregnancies among tertiary students is increasing globally. About 16 million young women between the ages of 15 years and 19 years around the world became mothers and two million girls under the age of 15 years are reported to be pregnant every year. South African universities continue to report high rates of student pregnancies, and are looking for solutions to the crisis that female students are facing. Aim: The purpose of the study was to explore the experiences of pregnant and parenting students. Setting: At a university in Gauteng province, South Africa. Methods: A qualitative, exploratory and descriptive design was used in a study that was conducted at a university in Gauteng province, South Africa. Undergraduate pregnant and parenting students were sampled purposively, and the sample size was 15 participants. Semi-structured interviews were used to collect data and data were analysed using thematic analysis. Results: The findings of the study produced four themes, namely emotional experience during pregnancy, academic challenges during parenting, experiences during antenatal care, and students' resilience during pregnancy and parenting. Conclusion: Pregnant and parenting students require emotional, academic and social support from the university and other stakeholders. The university should offer on-campus medical services such as antenatal care and provide academic support for pregnant and parenting students to help them achieve their academic objectives. Contribution: This study highlights the importance of developing support programmes that focus on pregnant and parenting students in universities.